Scoping study of the economics of CO2 transport and storage options for steel manufacturing emissions in eastern Australia. (February 2022) - Fimbres Weihs, G.A.; Ho, M.; Kambanis, J.; Wiley, D.E.
Highlights: Scoping economic comparison of pipeline and ship CO2 transport in eastern australia. CO2 captured from iron and steel plant located in port Kembla, NSW. Estimated costs are lowest for the hub pipeline transport. The shipping transport option presented highest cost. There is still a case to be made for ship transport if the project duration is short. Abstract: The main source of CO2 emissions in an integrated steel manufacturing plant comes from the need to use a carbon source, often coal, in the steel making process. Amongst the pathways for reducing CO2 emissions is the application of carbon capture, transport and storage (CCS) technologies. This paper presents a scoping-level economic evaluation of transport and storage location options for CO2 captured from an iron and steel plant located in Port Kembla, NSW, Australia. Pipeline (single and hub) and ship transport of CO2, and two injection locations are considered. Estimated costs are lowest for the hub transport case injecting at the Gippsland basin (∼35% lower than for single source cases) and highest for the shipping case. For the single-source cases, transport via pipeline to the Darling basin is slightly more attractive in terms of unit costs. The hub transport cases were between two-thirds and half of the cost of the shipping case. Although the shipping transport option presented the highest cost of the cases considered, there is still a case to be made for ship transport if the project duration is short.